Ashantee War - The House of Commons (My University, 1864)
Copies or Extracts of any Despatches from the Governor of the Gold Coast explaining the cause of the War with the King of Ashantee; of any Despatches from the Secretary of State to the Governor of the Gold Coast, directing him to prosecute the War; Returns of the Expense already incurred in this War; and, of the Number of Officers and European Troops landed at Cape Coast Castle, and Date of Landing.
Keywords: Despatches; Extracts; Cape Coast Castle; War